Long-term persistence with evolocumab treatment and sustained reductions in LDL-cholesterol levels over 30 months: Final results from the European observational HEYMANS study. (February 2023) - Ray, Kausik K.; Bruckert, Eric; Peronne-Filardi, Pasquale; Ebenbichler, Christoph; Vogt, Anja; Bridges, Ian; Sibartie, Mahendra; Dhalwani, Nafeesa
Abstract: Background and aims: Variability in low-density lipoprotein-cholesterol (LDL-C) level control at a population level is associated with poor cardiovascular outcomes. Limited data exist on LDL-C level variability or long-term persistence with the monoclonal antibody evolocumab in routine clinical practice. Using data from the HEYMANS registry, this analysis aimed to assess evolocumab persistence and discontinuation over 30 months of evolocumab treatment and to evaluate at a population level the variability in LDL-C level reductions during the study period. Methods: HEYMANS was a prospective registry of adults initiating evolocumab in routine clinical practice in 12 European countries. Data were collected for up to and including 6 months before evolocumab initiation and up to 30 months after. Evolocumab discontinuation was analysed for two time periods: 0–12 months and 12–30 months. Results: In total, 1951 patients were included in the study. The median reduction in LDL-C levels was 58% within 3 months after evolocumab initiation; this reduction was maintained over 30 months. More than 90% of patients continued receiving evolocumab at 12 months and 30 months of follow-up. Of patients with an LDL-C level measurement during follow-up, approximately 85% achieved a ≥30% reduction from baseline at each follow-up visit and approximately 60% achieved a ≥50% reduction. Conclusions: Evolocumab therapy was associated with sustained LDL-C level reductions up to 30 months, and persistence with evolocumab remained high, both at 12 and 30 months. Expanding the use of monoclonal antibodies such as evolocumab could provide improvements in LDL-C level control at a population level in European clinical practice. Graphical abstract: Image 1 Highlights: Data from the HEYMANS registry were used to assess the use of evolocumab over time. Evolocumab was associated with sustained LDL-C reductions for up to 30 months. Evolocumab was associated with an approximately 60% reduction in LDL-C levels. Over 90% of patients continued receiving evolocumab at 12 months and 30 months. Consistent reductions in LDL-C were achieved with evolocumab in clinical practice.